2013
DOI: 10.3989/gya.084612
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation of methyl esters derived from Jatropha oil: An optimization study

Abstract: RESUMEN Epoxidación de ésteres metílicos derivados del aceite de Jatropha: Optimización del estudioSe ha evaluado la optimización de la reacción de epoxidación de ésteres metílicos obtenidos a partir de aceite de Jatropha. Se ha empleado para el diseño experimental una metodología de superficie de respuesta (RSM), basada en un diseño compuesto central giratorio (CCRD). Cuatro variables de la reacción fueron evaluadas: relación molar peróxi-do de hidrógeno/C=C, relación molar ácido fórmico/C=C, temperatura de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…These results confirm that the process of epoxidation for both oils in natura occurred (Adhvaryu and Erhan, 2002;Petrovic et al, 2002;Dinda et al, 2008;Meyer et al, 2008;Milchert et al, 2010;Mushtaq et al, 2013). It is observed that the presence of the additive increases the viscosity of the fluids of passion fruit oil in natura without additives (PFO) and the moringa oil in natura without additive (MO), and that after its epoxidations, this increase also occurs.…”
Section: Resultssupporting
confidence: 92%
“…These results confirm that the process of epoxidation for both oils in natura occurred (Adhvaryu and Erhan, 2002;Petrovic et al, 2002;Dinda et al, 2008;Meyer et al, 2008;Milchert et al, 2010;Mushtaq et al, 2013). It is observed that the presence of the additive increases the viscosity of the fluids of passion fruit oil in natura without additives (PFO) and the moringa oil in natura without additive (MO), and that after its epoxidations, this increase also occurs.…”
Section: Resultssupporting
confidence: 92%
“…The spectrum of CJO, which consists mainly of triglycerides, was generated as a baseline prior to reaction. The spectrum associated with a typical glyceride profile was compared with previous works (Kouame et al, 2012;Mushtaq et al, 2013). The spectrum of CJO showed the existence of unsaturation in the range of 5.27-5.32 ppm and 2.00 ppm and glycerol in the range of 4.0-4.27 ppm.…”
Section: Nmr Spectral Analysis 1 H Nmrmentioning
confidence: 87%
“…The role of hydrogen peroxide is directly associated with acetic acid in the formation of peroxyacetic acid. However, its role is more significant because it is consumed during the reaction, but acetic acid is regenerated after their oxygen atom is utilized (Goud et al, 2010;Mushtaq et al, 2013).…”
Section: Effect Of Molar Ratio Of Hydrogen Peroxide To Unsaturationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, experimental designs and statistical analyses have been employed to evaluate the effects of and to optimize the epoxidation process conditions. Response surface methodology, a statistical method often used in chemical and biochemical engineering, was employed to optimize the epoxidation of vegetable oils such as rapeseed oil [21][22][23] and castor oil [24], as well as vegetable oil derivatives such as sucrose soyate [25] and methyl esters derived from castor oil [26], jatropha oil [27], and waste cooking oil [28]. Besides reducing the required experimental work, this approach enables not only the determination of the process conditions for reaching the highest epoxy yield, but also the evaluation of an interactive effect among the process conditions.…”
mentioning
confidence: 99%